Survey on arterial hypertension management: a report from the ESC Council for Cardiology Practice and the ESC Council on Hypertension. Issue 2 (7th August 2021) - Mancusi, Costantino; de Simone, Giovanni; Asteggiano, Riccardo; Richter, Dimitri; Williams, Bryan; Ferrini, Marc
Abstract: Aims: To explore the management of hypertensive patients by general cardiologists a few months after the European Society of Cardiology (ESC)–European Society of Hypertension (ESH) Guidelines publication. Methods and results: A survey based on a 26-point questionnaire was sent to ∼69 000 worldwide ESC members, a few months after the ESC–ESH Guidelines publication. A total of 1458 responses were collected via a web-based form. Among them, 68% were men, 48% were below 45 years old, and 60% were from Europe. Current guidelines have been read, at least partially, by 92.8%. Measurement of blood pressure (BP) is mostly done using the auscultatory method (58.8%) while unattended BP is rarely performed. Different bladder cuffs are not available for different arm circumferences for 27% of responders. Routine workup in hypertensive patients includes more often 12 leads ECG (97.7%) and echocardiography (79.6%). Only 30.9% of responders systematically assess the cardiovascular risk by the SCORE system and orthostatic hypotension is systematically researched by only 39.1%. Respondents consider that BP target of 140/90 mmHg is achievable in 60–80% of patients and 130/80 mmHg in 40–60%. Guidelines are considered too tight to be achievable by 15.6%, while 77.4% consider they are exactly right. Low patient's compliance, awareness of hypertension (HT) risk, and, at a lower degree, physician inertia, represent the main treatment challenges in reaching BP goals to most respondents, while treatment effectiveness is not in question. The present survey demonstrates specific gaps in HT management that need attention in clinical practice. Graphical Abstract: